Chemistry and Technology of Lubricants - Mortier, Roy M.; Fox, Malcolm F.; Orszulik, Stefan (Springer Netherlands : Imprint: Springer, 2010)
The Chemistry and Technology of Lubricants describes the chemical components that contribute to the formulation of liquid lubricants followed by discussion of lubricant technology for specific applications. The individual components are described in Part I: Base Fluids and in Part II: Additives. Part I covers the manufacture and properties of the most common base fluid types derived either from mineral oil or by synthesis, including products from natural gas via gas-to-liquid processes. Part II describes the manufacture, mode of action and performance of the additives that are used to supplement and enhance the performance of base fluids. The use of vegetable oils is also included. Part III: Applications covers the major areas of application of liquid lubricants and each chapter is focused on technology requirements specific to the application. The book is completed by Part IV: Performance which describes more generic technology related to aspects of condition monitoring, environmental impact and industry testing. The Chemistry and Technology of Lubricants will be of use to those in both academia and industry who are working on lubricants or related areas of research and development. It will be of particular relevance for those in industry who are involved with lubricant additives, formulation and testing as well as those who are concerned with the use and specification of lubricants. Academic interest will include related chemistry and applied chemistry research as well as certain areas of mechanical engineering such as surface engineering and tribology.